Effectiveness Of Dengue Fever Education On Knowledge, Attitudes, And Behavior Of Housewives - Swaidatul Masluhiya AF; Irma Irma (Universitas Tribhuwana Tunggadewi, 2025)
Dengue fever is one of the challenging public health problems in Indonesia with an increasing trend in cases. This study aims to evaluate the effectiveness of dengue fever education on improving the knowledge, attitudes, and behaviors of housewives in preventing dengue fever. The study used a quasi-experimental design with a one-group pre-test post-test approach. The respondents were chosen through a simple random sampling resulting 102 of 423 housewives living in Wiloso, Gondowangi Village, Malang Regency. The intervention was carried out through lectures using presentation media and 3M Plus videos. Data were collected using knowledge, attitude, and behavior questionnaires that had been previously validated through a Pearson correlation test (r = 0.519–0.816) and shown to be reliable with Cronbach’s Alpha values of 0.856 (knowledge), 0.778 (attitude), and 0.832 (behavior). Data analysis used the Wilcoxon Signed-Rank Test with a significance level of p 0.05. The results showed a significant increase in knowledge (p = 0.000) and behavior (p = 0.000), while attitudes did not show significant changes (p = 0.064). This indicates that education can improve understanding and practice of dengue prevention, but attitude requires more intensive and sustained intervention. This study confirmed that empowering housewives as agents of change at the household level is very important to control dengue. The results of this study are expected to serve as a reference in the development of community-based public health education strategies in endemic areas.